Revitalizing industrial growth in Pakistan : trade, infrastructure, and environmental performance - Sánchez Triana, Ernesto (Directions in development (Washington, D.C.). Private sector development., 2014)
Pakistan's development efforts are guided by its 2011 Framework for Economic Growth, which identifies actions needed to create a prosperous, industrialized Pakistan through rapid and sustainable development. Industrialization has the potential to drive Pakistan's economic growth and contribute significantly to meeting both economic and human development goals in Pakistan. Expansions of industrialization activities, whether in highly developed or developing countries, can be stimuli for intense debate about such projects' benefits and costs to the region in which they are to be located, to the.